Konstanty i peremennye kulʹtury v âzykovom prostranstve ukrainskih media - Ševčenko, Larisa I. (Stylistyka, 2019)
The article deals with the question if the categories of “constant” are “variables” in a projection on media communication. Status of these categories in science, their features in a natural-science and human comprehension are examined. Constants and variable units of culture are analyzed in their dynamic development. Media communication is interpreted in the context of representation of mass language awareness through the active processes of language development. The author pays attention to the invariance of cultural constants in the media, their certain semantic and functional diffusion in relation to the variable units of culture in media communication.